MONITORING PELAKSANAAN TUJUAN PEMBANGUNAN BERKELANJUTAN OLEH BADAN PERENCANAAN PEMBANGUNAN DAERAH PENELITIAN DAN PENGEMBANGAN PROVINSI RIAU (STUDI TUJUAN PERTAMA KEMISKINAN DI KOTA PEKANBARU) - Ghina Sonia; Eko Handrian (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2023)
Monitoring the implementation of the sustainable development goals is observing the progress of achieving the sustainable development goals from time to time to measure the progress of achieving the targets. The purpose of this study aims to identify and explain the monitoring of the implementation of sustainable development goals by the Regional Development Planning Agency for Research and Development of Riau Province (Study of First Poverty Goals in Pekanbaru City). This research was conducted at the development planning agency in the Riau province research and development area. This type of research uses qualitative research methods with data collection techniques, namely interviews, observation, and documentation. The data analysis technique in this study is by means of descriptive analysis and using the triangulation method. The factors that hinder monitoring the implementation of sustainable development goals (the first objective study of poverty in Pekanbaru City) are human resources, budget, time resources, unavailability of adequate reports, coordination and cooperation between agencies. Based on the results of this study, monitoring of the implementation of sustainable development goals by the regional development planning agency for research and development in Riau province (the first objective study of poverty in Pekanbaru City) has been carried out but has not been optimal, this is related to the timeliness of monitoring implementation and limited resources in conducting monitoring. Advice that can be given is by utilizing technology-based use to make it more effective and efficient.